2017
DOI: 10.1103/physrevmaterials.1.024408
|View full text |Cite
|
Sign up to set email alerts
|

Successive field-induced transitions in BiFeO3 around room temperature

Abstract: The effects of high magnetic fields applied perpendicular to the spontaneous ferroelectric polarization on single crystals of BiFeO3 were investigated through magnetization, magnetostriction, and neutron diffraction measurements. The magnetostriction measurements revealed lattice distortion of 2 × 10 −5 , during the reorientation process of the cycloidal spin order by applied magnetic fields. Furthermore, anomalous changes in magnetostriction and electric polarization at a larger field demonstrate an intermedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
1
16
2
Order By: Relevance
“…This approach has been realized in a wide range of systems, including the switching dynamics of single-domain nanoparticles by stress [5], by ultrafast acoustic pulses [6], and by tensile strain induced from a piezoelectric substrate [7][8][9]. Strain engineering techniques have been successfully employed to manipulate magnetic moments in perovskite-based multiferroics [10][11][12][13][14][15], multiferroic thin-film heterostructures [16], and in nanowires [17]. A change in the magnetic anisotropy governed by strain is clearly demonstrated in ferromagnetic-ferroelectric [18,19] and ferrite-ferroelectric heterostructures [20] due to structural or metal-insulator [21] phase transformations in the material.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been realized in a wide range of systems, including the switching dynamics of single-domain nanoparticles by stress [5], by ultrafast acoustic pulses [6], and by tensile strain induced from a piezoelectric substrate [7][8][9]. Strain engineering techniques have been successfully employed to manipulate magnetic moments in perovskite-based multiferroics [10][11][12][13][14][15], multiferroic thin-film heterostructures [16], and in nanowires [17]. A change in the magnetic anisotropy governed by strain is clearly demonstrated in ferromagnetic-ferroelectric [18,19] and ferrite-ferroelectric heterostructures [20] due to structural or metal-insulator [21] phase transformations in the material.…”
Section: Introductionmentioning
confidence: 99%
“…Since |D 2 | K Z , the spins lie primarily in the XY plane with S iZ ≈ 0. The spin canting induced by the DM interaction and by magnetic fields [15] up to about 35 T is less than 2 • . Consequently, the zero-order spin state is S 1 ≈ −S 2 and (S 1 − S 2 ) ⊥ B.…”
Section: Modelmentioning
confidence: 88%
“…Other modes do not exhibit clear changes when entering this intermediate state. Theoretical studies [69] and neutron diffraction spectroscopy [15,70] reveal that the intermediate state in magnetic field B ⊥ Z is a conical spin structure with ordering vector along the magnetic field. While earlier measurements suggested that it disappears at low T [15], our data indicate that the intermediate state exists even at low T when B Z.…”
Section: Comparison With Thz Measurementsmentioning
confidence: 99%
See 2 more Smart Citations